Ceph cookbook : practical recipes to design, implement, operate, and manage Ceph storage systems /: practical recipes to design, implement, operate, and manage Ceph storage systems. (2017) - Umrao, Vikhyat; Singh, Karan; Hackett, Michael
No abstract available